Analysis and assessment of biomedical scientists’ needs for clinical laboratory: activity-based management as an evaluation methodology - Bizzoni, Claudia; Napolitano, Gavino; Cesa, Simonetta; Sacella, Luca; Bianciardi, Caterina; Ottomano, Cosimo; Mancini, Rita; Da Rin, Giorgio (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionHealthcare systems have to protect citizens’ health by developing models combining concepts of efficiency, effectiveness and quality of care. The post-Covid-19 pandemic context has highlighted the relevance of efficiently managing and allocating human resources. In this scenario, the analysis and calculation of personnel needs take on strategic importance. The project aims to suggest a methodology to define the needs of Biomedical Scientists. The goal is to create a standard model adaptable to different contexts.MethodsThis project, developed in cooperation with the Italian Society of Clinical Biochemistry and Clinical Molecular Biology, has created a new format following the “Activity Based Management” approach. It is characterized by continuous improvements, based on analysis of processes, broken down into sub-processes and activities. After the phase of format development, a phase of application to different contexts, such as biochemistry and the hematology sectors, followed.ResultsThe suggested methodology allows to estimate the number of Full Time Equivalents necessary for the management of the laboratory processes. Furthermore, an objective and analytical data is obtained, because it is based on timely numerical surveys that included productivity and execution times of the different activities.DiscussionUsing the format had a relevant impact on the analysis of the processes, their efficiency, and their possible improvement. This method allowed to evaluate and improve the analytical and “extra-production” activities, often underestimated but having a decisive role in the process. The proposed format can be considered a valid tool for laboratory managers to analyze and evaluating the needs of Biomedical Scientists in the laboratory. Activity Based Management allowed us to obtain precise and objective data and, at the same time, to focus on the main objective of any clinical laboratory: to create value for the patient by supporting diagnosis and treatment of paths through safe and reliable laboratory tests, which depends on a correct allocation of human resources.